KONSEP IMAN DALAM AGAMA ISLAM DAN KATOLIK - Solihun Azim (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
This research is entitled "The Concept of Faith According to Islam and Catholicism". As for the focus of this research, there are three sub-problems, namely: 1) what is the concept of faith according to Islam and Catholicism, 2) what is the similarity of faith according to Islam and Catholicism, 3) how is the difference in faith according to Islam and Catholicism. This type of research is comparatively qualitative. Comparatively qualitative is doing analysis to find and find similarities and differences in phenomena. This research is focused on the literatures and library materials related to the research title, namely the concept of faith according to Islam and Catholicism. The approach used is a normative theological approach. Has two sources of data consisting of: primary and secondary sources. The primary data sources in this study were sourced from the Koran and the Bible. Meanwhile, secondary data sources are supporting data such as books or other scientific works as well as various writings ranging from books, journals, websites, theses and so on. The results of this study are the similarities and differences in Islam and Catholic Christianity related to faith, namely; First, in terms of understanding about faith, these two religions have the same meaning, although they differ in terms of language, but have the same meaning if taken from the Qur'an and the Bible, because basically these come from the same root. Second, they both believe that God created the universe, and that God also created humans, although they differ in terms of the pronunciation and the way of believing in it. Third, these two religions both believe in several prophets and apostles who are believed to be messengers of God to reveal His glory to mankind. Like the prophet Adam and his wife Eve were the first humans created by God after creating the world. Fourth, believe in the Day of Judgment or life after death. which is clearly different from the way you believe in it or what you believe in.